MEDA- AN IMPORTANT MEMBER OF ASTAVARGA IS SUFFERING FROM IDENTIFICATION AND STANDARDIZATION (AYUSHDHARA, 2020)
Meda is one of the most important plants included in Astavarga. This plant is used in variety of Ayurvedic formulations such as Cyavanprasa. Dried underground parts (rhizomes) of this plant are used for medicinal purpose. This plant is claimed to possess rejuvenating, health promoting, immune system strengthening, anti-oxidant and cell regenerating properties. Also claimed to promote body fat, healing fractures, control fever, abdominal thirst, diabetic condition, seminal weakness, and as a cure for Vata, Pitta and Rakta dosa. The demand of this herb is increasing day by day but due to scarcity of this plant in wild, unaware about authentic botanical source, non-existing cultivation practices there is widespread problem of adulteration or substitution with other plants. The poor quality of raw material affect the quality of end product formed. So by taking into account the above situation this systematic review/ metadata analysis has conducted to find out adulteration in Meda.